The Phenomenology of Animal Life - Lestel, D.; Bussolini, J.; Chrulew, Matthew (University of New South Wales, 2014)
This paper presents a bi-constructivist approach to the study of animal life, which is opposed tothe realist-Cartesian paradigm in which most ethology operates. The method is elaborated through the examples of a knot-tying orangutan in a Paris zoo and chile-eating cats in a New York apartment. We show that, when grounded in the operational framework of the phenomenological approach, the interpretation of animal life acquires a much more robust character than is usually supposed.